Antiproliferative activity of Ethanolic Extract of Kembang Bulan (Tithonia diversifolia) Leaf on HeLa Cervical Cancer Cell Line - Puspitasari, Endah; Nuri, Nuri; Ningsih, Indah Yulia; Triatmoko, Bawon; Dianasari, Dewi (Indonesian Society for Cancer Chemoprevention, 2022)
Tithonia diversifolia has been showed to be cytotoxic and antiproliferative on colon cancer, glioblastoma, hepatoma, kidney cancer, breast cancer, lung cancer, melanoma, leukemia, ovary cancer, prostate cancer, and stomach cancer cell lines, but not on cervical cancer cells yet. Our research aimed to determine the cytotoxicity and antiproliferative activity of T.diversifolia leaf ethanolic extract on HeLa cervical cancer cell line. The cytotoxicity and the antiproferative activity assay were done using MTT method for 24 h for cytotoxic assay; and series of 24, 48, and 72 h for antiproliferative assay. The cytotoxic activity was analyzed using IC50, while the antiproliferative assay was analyzed based on the proliferation kinetics. All assays were done in triplicate. T.diversifolia leaf ethanolic extract exhibited strong cytotoxic activity on HeLa cervical cancer cell lines with the IC50 of 97.839±10.120 μg/mL. The cytotoxic activity was dose dependent. Based on the proliferation assay, the antiproliferative activity was stronger as the incubation time and the dose increases. T.diversifolia leaf ethanolic extract showed strong cytotoxic and antiproliferative activity on HeLa cervical cancer cell lines.Keywords: T.diversifolia leaf ethanolic extract, cytotoxicity assay, antiproliferative assay, HeLa cervical cancer cells.